Stringent adherence to a cytomegalovirus‐prevention protocol is associated with reduced overall costs in the first 6 months after kidney transplantation. Issue 3 (19th May 2015) - Matter‐Walstra, K.W.; Greiner, M.; Cusini, A.; Schiesser, M.; Ledergerber, B.; Fehr, T.; Mueller, N.J.
Abstract Background We previously documented that a stringent implementation of a preemptive cytomegalovirus (CMV) prevention protocol reduced the number of CMV disease episodes after kidney transplantation, when compared with a routine preemptive protocol. The impact on overall costs was assessed. Methods Cost comparisons were made for inpatient and outpatient costs and overall costs, using costs provided by the financial department. Variables were analyzed using the Wilcoxon rank‐sum test. A multivariable global linear model evaluated the effect of all co‐variables on cost differences. In Cohort 1 (n = 84), 74% were followed with a standard CMV preemptive protocol, and 26% received prophylaxis. In Cohort 2 (n = 74), an intensified CMV surveillance protocol was applied in 74% of patients, and 26% were given prophylaxis. Results Overall, Cohort 1 had significantly higher treatment costs as compared with Cohort 2 (mean Swiss francs [CHF] 104, 548 and CHF 76, 983, respectively, P = 0.0005). Excluding patients who received prophylaxis reduced these costs to CHF 89, 318 in Cohort 1 and CHF 73, 652 in Cohort 2. Outcome between Cohort 1 and 2 was comparable. Conclusion A stringent adherence to the CMV prevention protocol was associated with a significant reduction in overall costs. Whether this benefit is because of the demonstrated reduction in the rate of CMV disease needs to be assessed in a randomized trial.